BRAND ACTIVATION D’ nyon2 n’ D’ nyin2 - Septi Asri Finanda (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2017)
D'nyon2 n D'nyin2 (read: de nyon nyon en de nyin nyin) is a character with expressive lines form a sketch. D'nyon2 inspired by the face of Setyo Eko Widodo (Dodo), and the inspiration of D'nyin2 came from Septi Asri Finanda face (Septi). Dodo and Septi face is deformed into the shape of the sketches. The formation of face D'nyon2 n D'nyin2 begins with circular line as a deform step of the face Septi and Dodo by maintaining the character of each face. D'nyon2 n D'nyin2 applied to the commercial fashion products with the brand www.dnyonnyin.com. The presence of D'nyon2 n D'nyin2 to the commercial fashion products requires managing of an integrated of visual communications media to promote the products of www.dnyonnyin.com. Media management to an integrated visual communication is done as a brand awareness of the existence of D'nyon2 n D'nyin2 to the audience. Expressive power of D'nyon2 n D'nyin2 line sketches applied to the integrated visual communications media that will be designed with the underscore of the concept hand drawing illustration of the visual elements that are present in the form of drawings. Brand activation of D’nyon2 n D'nyin2 aims to increase brand awareness of the products www.dnyonnyin.com and bring up the interaction between www.dnyonnyin.com to the target audience so that it can create the experience of the target audience of www.dnyonnyin.com. Brand activation programs D’nyon2 n D' nyin2 is packed with activities sketch on stage with D'nyon2 n D'nyin2 that involves the audience to the event held thus stimulating the openness audience to try and buy the products of www.dnyonnyin.com. Brand activation of D'nyon2 n D'nyin2 tried plugging the image as a friend of the target audience with the benefits offered. The benefits provided are fun, humor, excitement when the target audience using the products of www.dnyonnyin.com. The existence taglines of D'nyon2 n D'nyin2 "Love Everybody Around You" became a message that is unique, different, and interesting as the positioning of the brand activation. Brand activation strategies D'nyon2 n D'nyin, first, is to seek insight consumer insight through the consumer journey of the target audience to find a point of contact. Second, determine the theme. Third, determine the media campaign. Determination an integrated visual communications media that will be designed aims to promote the products www.dnyonnyin.com to support the brand activation of D'nyon2 n D'nyin2 adjusted to outcomes data of the consumer journey of the specified target audience.Keywords : D’nyon2 n’ D’nyin2, Brand Activation